EFFECTIVE CONTRACT AS FACTOR OF THE MANAGEMENT OF SOCIAL-LABOUR RELATIONS IN HEALTHCARE - Игорь Петрович Салдан; Сергей Иванович Трибунский; Елена Владимировна Колядо; Владимир Борисович Колядо; Юрий Юрьевич Дорофеев; Валерий Николаевич Карташев (Медицина в Кузбассе, 2017)
Subject. A set of documents reflecting the contemporary legal and normative-methodical base for improvement of the management of social-labour relations in healthcare.